2021
DOI: 10.1080/13603116.2021.1991489
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting teachers' attitudes towards inclusion of students with autism spectrum disorder in Bosnia and Herzegovina

Abstract: Teachers' attitudes towards education of children with autism spectrum disorder (ASD) play a significant part in successfulness of the inclusive education. The goal of the present study was to examine the attitudes of teachers from Bosnia and Herzegovina (BIH) towards inclusion of students with ASD in general education classes. The sample for this study comprised 105 elementary school teachers (75 females, 30 males) from different parts of BIH. We examined the attitudes in relation to teachers' age, gender, ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…A key disabling factor identified in this study is that the participants' feelings of incompetence to address all learners' needs makes them believe that they are failing the learners and are consequently the barrier to the learners' successful learning. Other research studies (Wood and Olivier, 2010;Memisevic et al, 2021;Van Mieghem et al, 2022), conducted with teachers also identified feelings of fear, frustration, negativity and failure about their own ability to deal with disabilities which they then believed lead to lower academic standards. Thus, giving urgent attention to teachers in FSS's feelings of incompetence is critical as it can lead to a decreased capacity to perform, reduced efficiency, as well as poor health, mental and physical wellbeing and ultimately to a low sense of self-efficacy (Shulman, 2013;El-Sayed et al, 2014;Lynch, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key disabling factor identified in this study is that the participants' feelings of incompetence to address all learners' needs makes them believe that they are failing the learners and are consequently the barrier to the learners' successful learning. Other research studies (Wood and Olivier, 2010;Memisevic et al, 2021;Van Mieghem et al, 2022), conducted with teachers also identified feelings of fear, frustration, negativity and failure about their own ability to deal with disabilities which they then believed lead to lower academic standards. Thus, giving urgent attention to teachers in FSS's feelings of incompetence is critical as it can lead to a decreased capacity to perform, reduced efficiency, as well as poor health, mental and physical wellbeing and ultimately to a low sense of self-efficacy (Shulman, 2013;El-Sayed et al, 2014;Lynch, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, regardless of all the support and training South African teachers have already received regarding inclusive education, they still seem to feel disempowered and ineffective in the implementation of inclusive education (Engelbrecht et al, 2017;Nel, 2020;Walton and Engelbrecht, 2022). This results in negative attitudes, demotivation, a lack of self-control and a low sense of selfefficacy disabling them to teach effectively in an inclusive classroom (Bandura, 2006;Memisevic et al, 2021;Van Mieghem et al, 2022). In the South African context teachers have to deal with complex socio-, economic-, political-, cultural-and language situations both in and out of the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some teachers may feel unprepared or not confident enough to meet these students' educational needs. For instance, a recent study found that 62.9% of the teacher participants from Bosnia and Herzegovina agreed or strongly agreed that it was unfair to be asked to teach children with ASD in their mainstream school (Memisevic et al, 2021). Furthermore, 54.3% of these teachers believed that only teachers with special education training were able to help students with ASD in class (Memisevic et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent study found that 62.9% of the teacher participants from Bosnia and Herzegovina agreed or strongly agreed that it was unfair to be asked to teach children with ASD in their mainstream school (Memisevic et al, 2021). Furthermore, 54.3% of these teachers believed that only teachers with special education training were able to help students with ASD in class (Memisevic et al, 2021). It is therefore not surprising that teachers report less closeness and more conflicts in their relationships with students with ASD (Blacher et al, 2014;Prino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers' attitudes and knowledge are of better quality among specialized teachers, those who have received training in autism, and those who have already been in contact with autistic students (Desombre et al, 2019; Jury, Perrin, Rohmer, & Desombre, 2021; Memisevic et al, 2021; Park et al, 2010; Sanz‐Cervera et al, 2017; Shetty & Rai, 2014). Despite the importance of considering both teachers' knowledge and attitudes towards autism and inclusion, there are few tools with good psychometric qualities to assess these two concepts among a French‐speaking audience.…”
Section: Introductionmentioning
confidence: 99%